PENGARUH PENDIDIKAN KARAKTER DAN KONDISI SOSIAL EKONOMI ORANG TUA SISWA TERHADAP PRESTASI BELAJAR SISWA PADA SMP NEGERI 4 SATAP LIUKANG TANGAYA KABUPATEN PANGKEP - Khaidarsyah Khaidarsyah; Rego Dafila (Cross-border, 2021)
This research is a type of quantitative descriptive research. This research method uses quantitative research, the instruments used are questionnaires and documentation. The population in this study were students at SMP Negeri 4 Satap Liukang Tangaya, Pangkep Regency with a total sample of 22 people. Analysis of the data used in this study using multiple regression analysis, determination, T test and F test. The objectives of this study were to: (1) explain the effect of character education on student achievement at SMP Negeri 4 Satap Liukang Tangaya, Pangkep Regency (2). the influence of the socio-economic conditions of parents on student achievement at SMP Negeri 4 Satap Liukang Tangaya, Pangkep Regency, (3) explaining the influence of character education and socioeconomic conditions of parents of students on student achievement at SMP Negeri 4 Satap Liukang Tangaya, Pangkep Regency. Collecting data using questionnaires, documentation and observation. The results of the research that have been done state that partially (1) Character Education has a positive effect on increasing student achievement. (2) the economic conditions of parents have no effect on student achievement. Meanwhile, simultaneously (3) Character Education and the economic conditions of parents jointly affect the increase in student learning achievement.